Protein C Global Assay in the Evaluation of Women with Idiopathic Pregnancy Loss - Sarig, Galit; Lanir, Naomi; Hoffman, Ron; Brenner, Benjamin (Thrombosis and Haemostasis, 2002)
Since the majority of thrombophilic defects in women with pregnancy loss are in the protein C pathway, we have prospectively determined the diagnostic value of a protein C global assay in 60 consecutive women with pregnancy loss compared to 61 controls. Protein C activation time normalized ratio (PCAT-NR) in pregnancy loss women was significantly lower than controls (0.74 ± 0.16 vs. 0.99 ± 0.2; P <0.0001). PCAT-NR lower than cut off level of 0.8 were found in 42/60 (70%) of PL women compared to 7/61 (11%) of controls (OR = 18.0, 95% CI: 6.3-53.4, P < 0.0001).Cut-off level of 0.8 successfully identified all pregnancy loss women with abnormality in the protein C pathway (12 factor V Leiden, 7 APC-Resistance without factor V Leiden, 15 low levels of protein S and 1 of protein C). Moreover, PCAT-NR below 0.8 was documented in 15/29 (52%) of PL women without thrombophilic risk factor compared to 3/55 (5%) of controls (OR = 18.6, 95% CI: 4.2-95.2, P <0.0001).These results suggest that ProC Global may be useful as a screening test for protein C pathway abnormalities and may serve as a new thrombophilic risk factor in women with pregnancy loss.
Keywords: Protein C pathway; thrombophilia; pregnancy loss